BIOLOGÍA DEL PICUDO DE LA YEMA DEL MANZANO AMPHIDEES LATIFRONS (SHARP) (COLEOPTERA: CURCULIONIDAE) - Guerrero Rodríguez, Eugenio; Lezcano Barrozo, José Ángel; Sánchez Valdez, Víctor Manuel; Corrales Reynaga, Jorge; Landeros Flores, Jerónimo (Instituto de Ecología, A.C., 2022)
The biological cycle of Amphidees latifrons (Sharp) was determined and estimated in degree days (°D), whit lower treshold of 5°C. In total required 4,564 HU, which required 326 days; this events by separated are: preoviposition 280 HU (20 days), incubation and hatched 350 HU (25 days), larval stages 1,260 HU (90 days), pupae 420 HU (30 days) and adults. In the orchard, the populations of L2, L3 and pupae were obtained from February to May, the larvae were eating secondary roots of apples. The adults were present all days of the year, the main population was observed from September to November, eating in this period leaves, and during November to February eating apple buds and vegetative buds. The adult is parthenogenic, does not have flying wings, and has nocturnal behaviour.